Analytical thinking style leads to more utilitarian moral judgments: An exploration with a process-dissociation approach. (1st September 2018) - Li, Zhongquan; Xia, Shiyu; Wu, Xiaoyuan; Chen, Zhaoyu
Abstract: Although several studies have indicated that the analytical thinking style led to more utilitarian moral judgments, the mechanism underlying this finding was still not clear. We explored the relationship between thinking modes and moral judgment with a process-dissociation approach in two studies. In Study 1, participants were first asked to make a judgment on the moral appropriateness of the agent's utilitarian action on four moral dilemmas, and then they were asked to recall the extent to which the judgment was based on intuitive versus analytical thinking mode. In Study 2, participants were instructed to use the intuitive or the analytical thinking mode during moral judgment on six pairs of moral dilemmas. The results of both studies indicated that the analytical thinking mode led to utilitarian moral judgments. The results of Study 2 also indicated the utilitarian inclinations mediated the association between thinking modes and moral judgment.